An Overview of Improving Logistics Processes in Health Facilities - Zdenek Smutny; Katerina Svandova (ITEGAM-JETIA)
Internal logistics processes in health facilities are complex and important to ensure health services and high-quality patient care. Therefore, the review is focused on issues, solutions and challenges related to logistic processes in health facilities. This review follows the PRISMA guidelines. Relevant studies were searched in the citation databases Web of Science and Scopus. The search was limited to articles published in English between 2000 and 2023. Based on the search and selection process, a total of 26 articles were included in the review. A qualitative content analysis was carried out. In this period analytical research dominates over design research. In terms of research strategies, a qualitative approach is preferred. The problem contexts addressed in the articles have been divided into five thematic areas. Most articles can be classified in the area dealing with sociotechnical interaction in internal logistics. The solutions presented in found articles can be divided according to the type of artefact into (1) formal approaches focused on models and algorithms, and (2) sociotechnical approaches focused on design of implementation frameworks. Challenges include the comparison of proposed solutions or their configurations in different problem contexts and regions. Further research should focus on organisational issues in internal logistics. Although the improvement of internal logistics in health facilities is a topic that has seen an increase in researcher interest over the last decade, there is a need to build a theoretical base on the findings of this research, which has been done only to a very limited extent. In terms of the use of new technologies, high persistence in the use of older IT-based solutions and rigidity can be observed in the implementation of new solutions.